Metal organic framework spraying antibacterial hydrogel with light response capability as well as preparation method and application of metal organic framework spraying antibacterial hydrogel
By doping copper ions into the metal organic frame and combining photothermal effect, a photo-responsive metal organic frame sprayed with antibacterial hydrogel was developed, which solved the problem of ineffectiveness of traditional antibiotics on drug-resistant strains and achieved efficient antibacterial and wound healing for skin lesions.
Patent Information
- Application Number
- CN202411907324.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-01
AI Technical Summary
In the prior art, when dealing with skin lesions, antibacterial materials are highly toxic and drug-resistant strains are resistant to traditional antibiotics, resulting in hindering wound healing.
A metal organic frame with photoresponsiveness spray-coated antibacterial hydrogel was developed to enhance antibacterial properties by doping copper ions into zinc-based metal organic frames, combining photothermal effects and metal ion antibacterial activity, and using poloxamer as a gel matrix to make a thermosensitive hydrogel dressing.
After contacting the skin, the hydrogel quickly forms a transparent, breathable, and antibacterial hydrogel. It can degrade itself after 24 to 36 hours. It has the characteristics of convenient operation, painless administration and adaptation to wounds of any shape, which significantly promotes wound healing and is effective against drug-resistant strains.
Smart Images

Figure CN119733088A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of material science and biomedical technology, and specifically relates to a metal organic framework spray antibacterial hydrogel with light responsiveness, and a preparation method and application thereof. Background Art
[0002] When skin damage occurs, timely and effective treatment is essential for wound healing. The growth of microorganisms is the main cause of bacterial infection and inhibition of wound healing. Although antibiotics have significant antibacterial effects, long-term use may lead to bacterial resistance, further aggravating wound healing problems. Therefore, non-antibiotic antibacterial drugs have become the mainstream in the research of promoting skin wound healing.
[0003] Metal organic frameworks (MOFs) are a new type of artificially synthesized multifunctional material with customizable structure, which is widely used in the biomedical field. At present, the antibacterial ability of MOFs depends not only on its loading of antibacterial materials, but also on the decomposition and release of its own antibacterial active ingredients, as well as photothermal and photodynamic effects, neither of which involves the use of antibiotics, and is expected to be used to combat various drug-resistant strains.
[0004] Copper-based MOFs have the best antibacterial properties thanks to the high antibacterial activity of copper ions. However, the high toxicity of copper ions makes copper-based MOFs not an ideal in vivo antibacterial material. Therefore, more and more research tends to develop the photothermal and photodynamic effects of MOFs. Currently, ZIF-8 has been shown to have good photoresponsiveness, but the antibacterial ability of zinc ions themselves is weak. Bimetallic MOFs are porous structures composed of two metal ions and an organic ligand, which show better synergistic effects while exhibiting the same excellent properties as single metal MOFs. However, to date, there are still few studies on their biomedical applications.
[0005] Compared with most traditional wound dressings, hydrogel dressings have high water content and high water absorption, which can promote the exchange of nutrients, thereby relieving pain and limiting drug extravasation. In recent years, thermosensitive hydrogels have attracted widespread attention due to their excellent reversible liquid-solid transition properties. This type of hydrogel is easy to operate and carry, has good mechanical properties and adhesion, can be sprayed for drug delivery, is simple to operate, fast to use, accurately delivers drugs, forms gel in situ, and is painless, avoiding secondary damage. Summary of the invention
[0006] In view of the above problems existing in the prior art, the purpose of the present invention is to provide a metal organic framework spray antibacterial hydrogel with light responsiveness and its preparation method and application, successfully doping copper ions into zinc-based metal organic frameworks, improving the light responsiveness of metal organic frameworks, combining the photothermal effect of metal organic frameworks with the antibacterial activity of metal ions, and enhancing the antibacterial properties of naringenin-loaded metal organic framework composite materials. Poloxamer is used as a gel matrix to make a thermosensitive hydrogel dressing, which can be directly sprayed on the wound surface and converted into a gel state in situ at the affected area. The operation is convenient and painless, and with the help of near-infrared light irradiation, it can effectively promote wound healing.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A metal organic framework spray antibacterial hydrogel with light responsiveness consists of a thermosensitive hydrogel matrix and a metal organic framework loaded with drugs; the thermosensitive hydrogel matrix is used as a solvent, and the mass concentration of the metal organic framework loaded with drugs is 0.8 to 1.2 mg / mL.
[0009] Furthermore, in the metal organic framework spray antibacterial hydrogel having light responsiveness, the metal organic framework loaded with drugs is a copper-doped metal organic framework loaded with naringenin, and its actual drug loading is 24-28%.
[0010] Furthermore, in the metal organic framework spray antibacterial hydrogel with light responsiveness, the thermosensitive hydrogel matrix is composed of poloxamer 407, poloxamer 188 and deionized water, the mass volume concentrations of poloxamer 407 and poloxamer 188 are 20-24% and 0-2%, respectively, and the total mass volume concentration of the two poloxamers is 20-26%.
[0011] The above-mentioned method for preparing a metal organic framework spray antibacterial hydrogel with light responsiveness includes the following steps: adding the drug-loaded metal organic framework to a thermosensitive hydrogel matrix at 0 to 4°C, vortexing for 5 to 10 minutes, and then ultrasonicating for 5 to 10 minutes in an ice water bath to obtain a drug-loaded metal organic framework spray antibacterial hydrogel.
[0012] Furthermore, the above-mentioned metal-organic framework spray-coated antibacterial hydrogel with light-responsiveness, the preparation method of the copper-doped metal-organic framework loaded with naringenin comprises the following steps: adding a copper-doped metal-organic framework and naringenin in a mass ratio of 0.5 to 2 into methanol, stirring the reaction in a closed manner at 20 to 40° C. for 1 to 7 hours, then centrifuging the generated product at a speed of 10,000 rpm for 10 minutes, washing with methanol, and drying in a vacuum oven at 55° C. for 12 to 24 hours to obtain the product.
[0013] Furthermore, the preparation method of the copper-doped metal-organic framework loaded with naringenin comprises the following steps: first, Cu(NO3)2·3H2O and Zn(NO3)2·6H2O are dissolved in methanol to prepare solution A, and then 2-methylimidazole is dissolved in methanol to prepare solution B, and solution B is added dropwise to solution A at 25°C and under nitrogen protection within 1 hour, and stirring is continued for 60 to 70 minutes, the resulting suspension is centrifuged at a speed of 7000 rpm for 10 minutes, and washed with methanol, and dried in a vacuum oven at 50 to 60°C for 12 to 24 hours to obtain the product.
[0014] Furthermore, in the above-mentioned method for preparing the copper-doped metal organic framework, the molar ratio of copper ions to zinc ions in the reactants is 10%, 15% or 20%.
[0015] Furthermore, in the above-mentioned method for preparing the copper-doped metal organic framework, the molar ratio of the total amount of copper ions and zinc ions to 2-methylimidazole is 1:8.
[0016] Furthermore, the above-mentioned metal organic framework spray antibacterial hydrogel with light responsiveness, the preparation method of the thermosensitive hydrogel matrix comprises the following steps: adding poloxamer 407 and poloxamer 188 to deionized water at 0-4°C, transferring the resulting mixture to a refrigerator and standing for more than 12 hours until poloxamer 407 and poloxamer 188 are completely dissolved to obtain a thermosensitive hydrogel matrix.
[0017] Any of the above-mentioned metal organic framework spray-coated antibacterial hydrogels with light responsiveness can be used for superficial wounds occurring in clinical practice and daily life.
[0018] The beneficial effects of the present invention are:
[0019] 1. The metal organic framework spray antibacterial hydrogel with light responsiveness described in the present invention is mainly used for superficial wounds in clinical and daily life, such as abrasions, cuts, etc.; the spray hydrogel is sprayed from the spray bottle in liquid form, and can quickly form a transparent, breathable, antibacterial hydrogel in situ on the wound surface, and degrade and fall off after 24 to 36 hours. At the same time, the spray antibacterial hydrogel has the characteristics of convenient carrying, simple operation, and painless administration. It can adapt to wounds of any shape and is suitable for all kinds of people.
[0020] 2. The present invention replaces part of the zinc ions with copper ions and combines with organic ligands to obtain a copper-doped metal organic framework. The copper ions have obvious light response ability and strong antibacterial ability. The copper doping can improve the antibacterial properties of the metal ions contained while improving the light response of the metal organic framework. A small amount of copper doping will not excessively increase cytotoxicity, and the copper-doped metal organic framework still has good biocompatibility. At the same time, naringenin is loaded into the copper-doped metal organic framework to prepare a composite material, thereby improving the antioxidant capacity of the composite material.
[0021] 3. The metal organic framework spray-coated antibacterial hydrogel with light responsiveness described in the present invention forms a hydrogel within 30 seconds after contacting the skin, has a fast gelation speed, high comfort, and does not affect daily behavior and activities. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is Cu 10% ZIF-8, Cu 15% ZIF-8 and Cu 20% Appearance morphology of ZIF-8.
[0023] Figure 2 It is Cu 15% SEM image of ZIF-8.
[0024] Figure 3 ZIF-8, Cu 10% ZIF-8, Cu 15% ZIF-8 and Cu 20% Infrared spectrum of ZIF-8.
[0025] Figure 4 ZIF-8, Cu 10% ZIF-8, Cu 15% ZIF-8 and Cu 20% XRD spectrum of ZIF-8.
[0026] Figure 5 ZIF-8, Cu 10% ZIF-8, Cu 15% ZIF-8 and Cu 20% XPS spectrum of ZIF-8, where a shows the peak position of zinc ions and b shows the peak position of copper ions.
[0027] Figure 6 This is a state diagram of the naringenin-loaded copper-doped metal organic framework antibacterial hydrogel prepared in Example 2 at different temperatures.
[0028] Figure 7 ZIF-8, Cu 15% ZIF-8、Nar@Cu 15% ZIF-8 and Nar@Cu15% Photothermal performance diagram of ZIF-8@Hydrogel.
[0029] Figure 8 ZIF-8, Cu 15% ZIF-8、Nar@Cu 15% ZIF-8 and Nar@Cu 15% Antibacterial activity of ZIF-8@Hydrogel against Escherichia coli (a) and Staphylococcus aureus (b), respectively.
[0030] Fig. 9 ZIF-8, Nar@Cu 15% ZIF-8 and Nar@Cu 15% The healing status of mouse wounds after being treated with ZIF-8@Hydrogel.
[0031] Fig.10 ZIF-8, Nar@Cu 15% ZIF-8 and Nar@Cu 15% Quantitative results of the healing status of mouse wounds after ZIF-8@Hydrogel was applied to them.
[0032] Fig.11 This is a preparation process and experimental design flow chart of a metal organic framework spray antibacterial hydrogel with light responsiveness in the present invention. DETAILED DESCRIPTION
[0033] Example 1 Naringin-loaded copper-doped metal organic framework antibacterial hydrogel (Nar@Cu 10% ZIF-8@Hydrogel 1)
[0034] (1) Copper-doped metal organic frameworks (Cu 10% Synthesis of ZIF-8
[0035] One-step synthesis by solvothermal method: 0.078g Cu(NO3)2·3H2O and 0.957g Zn(NO3)2·6H2O were dissolved in 40mL methanol to prepare solution A, where the molar percentage of Cu(NO3)2·3H2O to Zn(NO3)2·6H2O was 10% (the total of the two was 3.54mmol). Then 2.325g 2-methylimidazole was weighed and dissolved in 40mL methanol to prepare solution B. At room temperature and under nitrogen protection, solution B was added dropwise to solution A within 1 hour and stirred for 70 minutes. Centrifuge (7000rpm, 10min) and wash with methanol 3 times, and dry in a vacuum oven at 55°C for 24 hours to obtain reddish brown powder of Cu 10% ZIF-8.
[0036] (2) Naringenin-loaded copper-doped metal organic framework (Nar@Cu 10% Synthesis of ZIF-8
[0037] Synthesized by impregnation method: Cu 10% ZIF-8 (30 mg) was added to a beaker containing 40 mL of methanol and stirred until completely dispersed. Then 15 mg of naringenin (Nar) was added to the beaker and stirred under a closed magnetic stirrer at 20°C for 1 h. The resulting suspension was centrifuged (10000 rpm, 10 min), washed with methanol 3 times, and finally the precipitate was dried in a vacuum oven at 55°C for 24 h to obtain Nar@Cu 10% ZIF-8.
[0038] (3) Preparation of naringenin-loaded copper-doped metal organic framework antibacterial hydrogel
[0039] Poloxamer 407 at a concentration of 20% (w / v) was added to deionized water at 2°C, and the resulting mixture was transferred to a refrigerator and allowed to stand for 20 h until the poloxamer 407 was completely dissolved, thereby obtaining a poloxamer thermosensitive hydrogel matrix.
[0040] The copper-doped metal organic framework Nar@Cu loaded with naringenin was heated at 2 °C. 10% ZIF-8 was added to the poloxamer thermosensitive hydrogel matrix to make Nar@Cu 10% The concentration of ZIF-8 was 0.8 mg / mL, vortexed for 10 min, and then sonicated (800 w, 10 min) in an ice-water bath to evenly distribute the drug into the hydrogel network to obtain a naringenin-loaded copper-doped metal organic framework antibacterial hydrogel.
[0041] Example 2 Naringenin-loaded copper-doped metal organic framework antibacterial hydrogel (Nar@Cu 15% ZIF-8@Hydrogel 2)
[0042] (1) Copper-doped metal organic frameworks (Cu 15% Synthesis of ZIF-8
[0043] One-step synthesis by solvothermal method: 0.112g Cu(NO3)2·3H2O and 0.916g Zn(NO3)2·6H2O were dissolved in 40mL methanol to prepare solution A. At this time, the molar percentage of Cu(NO3)2·3H2O to Zn(NO3)2·6H2O was 15% (the total of the two was 3.54mmol). Then 2.325g 2-methylimidazole was weighed and dissolved in 40mL methanol to prepare solution B. At room temperature and under nitrogen protection, solution B was added dropwise to solution A within 1 hour and stirred for 70 minutes. Centrifuge (7000rpm, 10min) and wash with methanol 3 times, and dry in a vacuum oven at 55℃ for 24 hours to obtain reddish brown powder of Cu15% ZIF-8.
[0044] (2) Naringenin-loaded copper-doped metal organic framework (Nar@Cu 15% Synthesis of ZIF-8
[0045] Synthesized by impregnation method: Cu 15% ZIF-8 (30 mg) was added to a beaker containing 40 mL of methanol and stirred until completely dispersed. Then 30 mg of naringenin (Nar) was added to the beaker and stirred under a closed magnetic stirrer at 30°C for 4 h. The resulting suspension was centrifuged (10000 rpm, 10 min), washed with methanol 3 times, and finally the precipitate was dried in a vacuum oven at 55°C for 24 h to obtain Nar@Cu 15% ZIF-8.
[0046] (3) Preparation of naringenin-loaded copper-doped metal organic framework antibacterial hydrogel
[0047] Poloxamer 407 at a concentration of 22% (w / v) and poloxamer 188 at a concentration of 1% (w / v) were added to deionized water at 3°C, and the resulting mixture was transferred to a refrigerator and allowed to stand for 20 h until poloxamer 407 and poloxamer 188 were completely dissolved to obtain a poloxamer thermosensitive hydrogel matrix.
[0048] The copper-doped metal organic framework Nar@Cu loaded with naringenin was heated at 3 °C. 15% ZIF-8 was added to the poloxamer thermosensitive hydrogel matrix to make Nar@Cu 15% The concentration of ZIF-8 was 1.0 mg / mL, vortexed for 10 min, and then sonicated (800 w, 10 min) in an ice-water bath to evenly distribute the drug into the hydrogel network to obtain a naringenin-loaded copper-doped metal organic framework antibacterial hydrogel.
[0049] Example 3 Naringenin-loaded copper-doped metal organic framework antibacterial hydrogel (Nar@Cu 20% ZIF-8@Hydrogel 3)
[0050] (1) Copper-doped metal organic frameworks (Cu 20% Synthesis of ZIF-8
[0051] One-step synthesis by solvothermal method: 0.143g Cu(NO3)2·3H2O and 0.877g Zn(NO3)2·6H2O were dissolved in 40mL methanol to prepare solution A, where the molar percentage of Cu(NO3)2·3H2O to Zn(NO3)2·6H2O was 20% (the total of the two was 3.54mmol). Then 2.325g 2-methylimidazole was weighed and dissolved in 40mL methanol to prepare solution B. At room temperature and under nitrogen protection, solution B was added dropwise to solution A within 1 hour and stirred continuously for 70 minutes. Centrifuge (7000rpm, 10min) and wash 3 times with methanol, and dry in a vacuum oven at 55°C for 24 hours to obtain reddish brown powder of Cu 20% ZIF-8.
[0052] (2) Naringenin-loaded copper-doped metal organic framework (Nar@Cu 20% Synthesis of ZIF-8
[0053] Synthesized by impregnation method: Cu 20% ZIF-8 (30 mg) was added to a beaker containing 40 mL of methanol and stirred until completely dispersed. Then 60 mg of naringenin (Nar) was added to the beaker and stirred under a closed magnetic stirrer at 40°C for 7 h. The resulting suspension was centrifuged (10000 rpm, 10 min), washed with methanol 3 times, and finally the precipitate was dried in a vacuum oven at 55°C for 24 h to obtain Nar@Cu 20% ZIF-8.
[0054] (3) Preparation of naringenin-loaded copper-doped metal organic framework antibacterial hydrogel
[0055] Poloxamer 407 at a concentration of 24% (w / v) and poloxamer 188 at a concentration of 2% (w / v) were added to deionized water at 4°C, and the resulting mixture was transferred to a refrigerator and allowed to stand for 20 h until poloxamer 407 and poloxamer 188 were completely dissolved to obtain a poloxamer thermosensitive hydrogel matrix.
[0056] The copper-doped metal organic framework Nar@Cu loaded with naringenin was heated at 4 °C. 20% ZIF-8 was added to the poloxamer thermosensitive hydrogel matrix to make Nar@Cu 20% The concentration of ZIF-8 was 1.2 mg / mL, vortexed for 10 min, and then sonicated (800 w, 10 min) in an ice-water bath to evenly distribute the drug into the hydrogel network to obtain a naringenin-loaded copper-doped metal organic framework antibacterial hydrogel.
[0057] Example 4 Characterization of naringenin-loaded copper-doped metal organic framework antibacterial hydrogel
[0058] Figure 1The three copper-doped metal organic framework materials Cu synthesized in Examples 1, 2 and 3 are shown. 10% ZIF-8, Cu 15% ZIF-8 and Cu 20% The appearance and morphology of ZIF-8 powder. Figure 1 It can be seen that with Cu 2+ As the doping amount increases (from 10% to 20%), the color of the product changes from light red to dark brown. This is because Cu is reddish brown, and the color depth of the sample is related to Cu. 2+ There is a qualitative relationship between the content.
[0059] The Cu synthesized in Example 2 was observed by scanning electron microscopy. 15% The basic morphology and structural characteristics of ZIF-8 were observed, such as Figure 2 As shown, Cu 15% ZIF-8 exhibited the same regular dodecahedral structure as ZIF-8, with a particle size of 150 to 200 nm and a relatively smooth surface, proving that no impurities were generated during the synthesis process.
[0060] observe Figure 3 The infrared spectra of the three copper-doped metal organic frameworks synthesized in Examples 1, 2 and 3 all have peaks consistent with those of ZIF-8. The vibration of Zn-N can be observed in the far infrared region, indicating the successful coordination of HmIm and Zn. -1 The narrow peak at 2890 cm is the stretching peak of the =CH bond. The stretching vibration peak of the CH bond of HmIm is at 2890 cm -1 1147cm -1 The peak at 995cm is the in-plane bending vibration of the =CH bond. The in-plane bending of the =CH bond occurs at 995cm -1 The asymmetric bending of CH3 and CH2 is at 1384 cm -1 and 1427cm -1 The stretching peak of C=C bond is at 1456cm -1 The stretching peak of C=N bond is located at 1585cm -1 .
[0061] The eight main characteristic peaks of ZIF-8 are located at 7.3°, 10.4°, 12.7°, 14.7°, 16.4°, 18.0°, 24.5° and 26.7°. Figure 4 As shown in the figure, the diffraction peaks of the three copper-doped metal organic frameworks synthesized in Examples 1, 2 and 3 are similar to those of ZIF-8, indicating that Cu 2+ The doping and doping amount of Cu-doped MOFs will not affect the crystal structure of Cu-doped MOFs. The main reason is that and The ionic sizes of the ions are close to each other, and a small amount of doping does not affect the crystal configuration, thus maintaining the structural integrity of the ZIF-8 backbone. This similarity indicates that the copper-doped metal-organic framework has the same body-centered cubic lattice symmetry as ZIF-8.
[0062] In order to determine the elemental composition and valence state of the metal elements of the three copper-doped metal organic frameworks synthesized in Examples 1, 2 and 3, XPS was used to characterize them. Figure 5 As shown in the figure, the zinc electron binding energy peaks of ZIF-8 are located at 1044.8 eV and 1021.8 eV, respectively, indicating that the zinc element is mainly in the form of Zn 2+ The peak of zinc ions in the Cu-doped MOF is similar to that of ZIF-8. At the same time, the curve of the Cu-doped MOF has peaks at about 951.78 eV (2p1) and 931.88 eV (2p3), indicating that the synthesized Cu-doped MOF contains copper in the form of Cu + and Cu 2+ With the increase of copper doping, the peak becomes more prominent.
[0063] Example 5 Thermosensitivity of naringenin-loaded copper-doped metal organic framework antibacterial hydrogel
[0064] Select Nar@Cu synthesized in Example 2 15% ZIF-8@Hydrogel was further tested. In order to investigate the ejectability of the hydrogel, the gelation temperature of the antibacterial hydrogel prepared in Example 2 was tested.
[0065] like Figure 6 As shown, the hydrogel prepared in Example 2 is in liquid state at room temperature (25°C) and turns into gel state at 37°C, and the gel temperature is about 30°C. The temperature of normal naked skin is about 30°C. In view of the spray administration method, the hydrogel prepared in Example 2 (Hydrogel 2) is selected to prepare the copper-doped metal organic framework antibacterial hydrogel loaded with naringenin.
[0066] Example 6 Photothermal properties of naringenin-loaded copper-doped metal organic framework antibacterial hydrogel
[0067] In order to evaluate the photothermal performance of the antibacterial hydrogel, the photothermal conversion capacity of each component of the antibacterial hydrogel was tested. ZIF-8, Cu 15% ZIF-8、Nar@Cu 15% ZIF-8 and Nar@Cu 15% ZIF-8@Hydrogel (Example 2) Pure hydrogel was used as a blank control, and the temperature was recorded every 1 minute.
[0068] like Figure 7 As shown in the figure, all components showed photothermal effect. The temperature rose significantly at the beginning of near-infrared light irradiation, and then the temperature rose slowly. After ten minutes, the curve became stable and no longer heated up. 15% The temperature of ZIF-8 increased by 22 °C, while that of ZIF-8 increased by 15.6 °C, which is significantly lower than that of Cu 15% ZIF-8, Cu 15% The photothermal conversion ability of ZIF-8 is better than that of ZIF-8, and it is expected to play a photothermal sterilization role.
[0069] Example 7 Antibacterial properties of naringenin-loaded copper-doped metal organic framework antibacterial hydrogel
[0070] Pure hydrogel and ZIF-8 were used as control groups. 15% ZIF-8、Nar@Cu 15% ZIF-8、Nar@Cu 15% ZIF-8@Hydrogel (Example 2) was tested to further explore the antibacterial effect of the obtained preparation.
[0071] In the absence of NIR, the control group of E. coli and Staphylococcus aureus grew well on solid agar. When exposed to NIR, there was almost no change in bacterial survival, proving that 808nm NIR itself does not kill bacteria.
[0072] like Figure 8 As shown, ZIF-8 and Cu 15% The inhibition rates of ZIF-8 against Escherichia coli under near-infrared conditions were 65.3% and 82.3%, respectively, while Nar@Cu 15% The inhibition rate of ZIF-8@Hydrogel against Escherichia coli under near-infrared conditions was 90.9%. The reason for this difference is that in addition to the antibacterial effect of Nar, the sustained release of drugs in the hydrogel also achieved a long-term antibacterial effect. 15% The inhibition rates of ZIF-8 against Staphylococcus aureus under near infrared were 67.2% and 85.5%, respectively, while Nar@Cu 15% The inhibition rate of ZIF-8@Hydrogel against Staphylococcus aureus under near-infrared light was 93.0%. In addition, the results showed that the antibacterial rates of the experimental groups followed the same rule regardless of whether near-infrared light was applied, that is, from large to small: Nar@Cu 15% ZIF-8@Hydrogel>Nar@Cu 15% ZIF-8>Cu 15% ZIF-8>ZIF-8.
[0073] Example 8 Naringenin-loaded copper-doped metal organic framework antibacterial hydrogel promotes wound healing
[0074] Full-thickness wounds were established in mice to investigate the effect of the prepared antibacterial hydrogel on promoting wound healing. Fig. 9 , 10 As shown, the wound healing trend of mice in the near-infrared light group during injury was better than that in the non-near-infrared light group.
[0075] At 3, 7, and 10 days, there were significant differences in wound healing between the groups with and without near-infrared light, which confirmed that Cu 15% The photothermal and photocatalytic effects of ZIF-8 played a positive role in the wound healing process. The healing effect of the group without near-infrared light was generally poor, but the healing trend was similar to that of the group with near-infrared light. The healing levels were as follows: Nar@Cu 15% ZIF-8@Hydrogel (Example 2) > Nar@Cu 15% ZIF-8>ZIF-8.
[0076] Under near-infrared light, the control group and Nar@Cu 15% The healing rates of the ZIF-8@Hydrogel groups on the 10th day were 81.71% and 99.91%, respectively, demonstrating that the prepared antibacterial hydrogel has an obvious effect in promoting wound healing.
Claims
1. A metal organic framework spray antibacterial hydrogel with light responsiveness, characterized in that: The components of the spray antibacterial hydrogel are composed of a thermosensitive hydrogel matrix and a metal organic framework loaded with drugs; the thermosensitive hydrogel matrix is used as a solvent, and the mass concentration of the metal organic framework loaded with drugs is 0.8-1.2 mg / mL.
2. The metal organic framework spray antibacterial hydrogel with light responsiveness according to claim 1, characterized in that: The drug-loaded metal organic framework is a copper-doped metal organic framework loaded with naringenin, and its actual drug loading amount is 24-28%.
3. The metal organic framework spray antibacterial hydrogel with light responsiveness according to claim 1, characterized in that: The thermosensitive hydrogel matrix consists of poloxamer 407, poloxamer 188 and deionized water. The mass volume concentrations of poloxamer 407 and poloxamer 188 are 20-24% and 0-2% respectively, and the total mass volume concentration of the two poloxamers is 20-26%.
4. The method for preparing a metal organic framework spray antibacterial hydrogel with light responsiveness as claimed in claim 1, characterized in that: The method comprises the following steps: adding a drug-loaded metal organic framework into a thermosensitive hydrogel matrix at 0-4°C, vortexing for 5-10 minutes, and then ultrasonicating for 5-10 minutes in an ice water bath to obtain a drug-loaded metal organic framework spray antibacterial hydrogel.
5. The metal organic framework spray antibacterial hydrogel with light responsiveness according to claim 2, characterized in that: The preparation method of the copper-doped metal-organic framework loaded with naringenin comprises the following steps: adding a copper-doped metal-organic framework and naringenin in a mass ratio of 0.5 to 2 into methanol, reacting with closed stirring at 20 to 40° C. for 1 to 7 hours, then centrifuging the generated product at a speed of 10,000 rpm for 10 minutes, washing with methanol, and drying in a vacuum oven at 55° C. for 12 to 24 hours to obtain the product.
6. The metal organic framework spray antibacterial hydrogel with light responsiveness according to claim 5, characterized in that: The preparation method of the copper-doped metal organic framework comprises the following steps: firstly, dissolving Cu(NO3)2·3H2O and Zn(NO3)2·6H2O in methanol to prepare solution A, then dissolving 2-methylimidazole in methanol to prepare solution B, adding solution B dropwise into solution A at 25°C and under nitrogen protection within 1 hour and continuously stirring for 60 to 70 minutes, centrifuging the generated suspension at a speed of 7000 rpm for 10 minutes, washing with methanol, and drying in a vacuum oven at 50 to 60°C for 12 to 24 hours to obtain a product.
7. The metal organic framework spray-coated antibacterial hydrogel with light responsiveness according to claim 6, characterized in that: The molar ratio of copper ions to zinc ions in the reactants is 10%, 15% or 20%.
8. The metal organic framework spray antibacterial hydrogel with light responsiveness according to claim 6, characterized in that: The molar ratio of the total amount of copper ions and zinc ions to 2-methylimidazole is 1:
8.
9. The metal organic framework spray antibacterial hydrogel with light responsiveness according to claim 3, characterized in that: The preparation method of the thermosensitive hydrogel matrix comprises the following steps: adding poloxamer 407 and poloxamer 188 into deionized water at 0-4°C, transferring the obtained mixture into a refrigerator and standing for more than 12 hours until poloxamer 407 and poloxamer 188 are completely dissolved to obtain a thermosensitive hydrogel matrix.
10. The metal organic framework spray-coated antibacterial hydrogel with light responsiveness as described in any one of claims 1-3 can be used for superficial wounds occurring in clinical practice and daily life.